Social Work Values: Are We Expected To Do The Impossible? - Antunes, Natalia (My University, 2004)
The social work profession is founded on a set of values that guide practice behaviours. These values are first adopted through social work education programs and are reinforced by the profession's cultural practices. However, many obstacles prevent social workers from adhering to social work values in practice. Personal, societal and organizational values that contradict social work values prevent social workers from being true to their mission. Unfortunately, many prevailing societal and organizational interests, such as patriarchal norms, capitalist business interests and managerial philosophies, are diametrically opposed to social work values. Thus, social workers are entrusted with an extremely difficult task; they are expected to manage numerous competing values, meet client needs, and work toward social change simultaneously. This study has attempted to accurately examine and depict the experiences of six female social workers, in order to gain a better understanding of social workers' struggles to manage competing principles. The participants have offered poignant examples of how social work values can be easily overridden by other value systems. This is particularly true in mainstream organizations, whose structures are less supportive of social work values. On the contrary community- based and feminist agencies appear to be more likely to support social work values, due to a variety of organizational factors. In addition, the findings highlight several implications for social work education, and raise questions about the need to change our current practice to be more inclusive of a variety of professionals, as well as clients. Furthermore, although the findings offer some hope in terms of the influence of social work values on ethical practice behaviours, they also highlight the fact that social work values and goals may simply be impossible to accomplish at all times.
Keywords: Social Work; Social Work